2015
DOI: 10.1002/cbf.3133
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Toll like receptor 3 induces spermatogonial stem cell apoptosis

Abstract: Germ cell apoptosis may be associated with the male infertility. The pathogenesis is to be further understood. Viral infection is one of the causative factors of apoptosis of the body cells. This study aims to investigate the role of activation of Toll like receptor (TLR)3 in the induction of germ cell apoptosis. In this study, spermatogonial stem cells (SSC) were isolated from C57BL/6 mouse testes. The expression of TLR3 on SSC was by RT-qPCR and Western blotting. polyinosinic-polycytidylic acid (Poly I:C) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…In contrast, Sendai virus (SeV) (136), MuV (746) and ZIKV (581) infection did not trigger an IFN-based antiviral response in differentiating rat and mouse germ cells. Nevertheless, poly IC induced the production of pro-inflammatory cytokines and type I IFN through TLR3 and MDA5 signaling in mouse germ cells, but to a much lower level than in Leydig cells (302,724). Exogenous IFN stimulation failed to induce a strong upregulation of ISGs in differentiating testicular germ cells, which is in line with the lack of functional type I IFN receptor expression in meiotic and post-meiotic mouse germ cells (136,581,602).…”
Section: Rodent Modelsmentioning
confidence: 68%
“…In contrast, Sendai virus (SeV) (136), MuV (746) and ZIKV (581) infection did not trigger an IFN-based antiviral response in differentiating rat and mouse germ cells. Nevertheless, poly IC induced the production of pro-inflammatory cytokines and type I IFN through TLR3 and MDA5 signaling in mouse germ cells, but to a much lower level than in Leydig cells (302,724). Exogenous IFN stimulation failed to induce a strong upregulation of ISGs in differentiating testicular germ cells, which is in line with the lack of functional type I IFN receptor expression in meiotic and post-meiotic mouse germ cells (136,581,602).…”
Section: Rodent Modelsmentioning
confidence: 68%
“…Briefly, an in vitro study revealed that Tlr3 activation by polyinosinic-polycytidylic acid, induced apoptosis of spermatogonia (Hu et al 2015). In addition, a study using Tlr2-and Tlr4-deficient mice showed that Tlr2 and Tlr4 contribute to the formation of autoimmune orchitis (Liu et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…By measuring apoptosis using the Annexin V, PI staining and TUNEL assay, our current results show values of the HU-treated groups were consistently higher than that of the control. A recent study found out that Toll like receptor 3/interferon regulatory factor 3 facilitated Fas ligand expression and induced apoptosis in spermatogonial stem cells (30). In another study, testicular germ cells of DBA/C57BL mice administered HU significantly increased expression of Fas, Fas ligand, Caspase-3, Caspase-8 and Caspase-9 related to apoptosis (31).…”
Section: Discussionmentioning
confidence: 99%